Diccionario de tareas para los padres - McLaughlin, Dan J. (Poway, Calif. : Damand Promotions, 2000)
Gives parents and students easy-to-understand explanations and easy-to-follow examples in all areas of language arts, math, science, and social studies.
Translation of: The parent's homework dictionary.
"Todos las respuestas, todos los cursos K-10"--Cover.
Includes bibliographical references and index.
Keywords: Education -- Parent participation; Language arts; Mathematics -- Study and teaching; Science -- Study and teaching; Social sciences -- Study and teaching; Home and school